6.4 Problems 301 to 400

Table 6.7: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

301

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+4 y^{\prime }-8 y = 0 \]

302

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }-3 y^{\prime \prime }-5 y^{\prime }-2 y = 0 \]

303

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }-54 y = 0 \]

304

\[ {}3 y^{\prime \prime \prime }-2 y^{\prime \prime }+12 y^{\prime }-8 y = 0 \]

305

\[ {}6 y^{\prime \prime \prime \prime }+5 y^{\prime \prime \prime }+25 y^{\prime \prime }+20 y^{\prime }+4 y = 0 \]

306

\[ {}9 y^{\prime \prime \prime }+11 y^{\prime \prime }+4 y^{\prime }-14 y = 0 \]

307

\[ {}y^{\prime \prime \prime \prime } = y^{\prime \prime \prime } \]

308

\[ {}y^{\prime \prime \prime }-5 y^{\prime \prime }+100 y^{\prime }-500 y = 0 \]

309

\[ {}y^{\prime \prime }+2 i y^{\prime }+3 y = 0 \]

310

\[ {}y^{\prime \prime }-i y^{\prime }+6 y = 0 \]

311

\[ {}y^{\prime \prime } = \left (-2+2 i \sqrt {3}\right ) y \]

312

\[ {}y^{\prime \prime \prime } = y \]

313

\[ {}y^{\prime \prime \prime \prime } = y^{\prime \prime \prime }+y^{\prime \prime }+y^{\prime }+2 y \]

314

\[ {}a \,x^{3} y^{\prime \prime \prime }+b \,x^{2} y^{\prime \prime }+c x y^{\prime }+y d = 0 \]

315

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+9 y = 0 \]

316

\[ {}x^{2} y^{\prime \prime }+7 x y^{\prime }+25 y = 0 \]

317

\[ {}x^{3} y^{\prime \prime \prime }+6 x^{2} y^{\prime \prime }+4 x y^{\prime } = 0 \]

318

\[ {}x^{3} y^{\prime \prime \prime }-x^{2} y^{\prime \prime }+x y^{\prime } = 0 \]

319

\[ {}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime }+x y^{\prime } = 0 \]

320

\[ {}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+x y^{\prime } = 0 \]

321

\[ {}x^{3} y^{\prime \prime \prime }+6 x^{2} y^{\prime \prime }+7 x y^{\prime }+y = 0 \]

322

\[ {}y^{\prime \prime }+16 y = {\mathrm e}^{3 x} \]

323

\[ {}y^{\prime \prime }-y^{\prime }+2 y = 3 x +4 \]

324

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 2 \sin \left (3 x \right ) \]

325

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = 3 x \,{\mathrm e}^{x} \]

326

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )^{2} \]

327

\[ {}2 y^{\prime \prime }+4 y^{\prime }+7 y = x^{2} \]

328

\[ {}y^{\prime \prime }-4 y = \sinh \left (x \right ) \]

329

\[ {}y^{\prime \prime }-4 y = \cosh \left (2 x \right ) \]

330

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = 1+x \,{\mathrm e}^{x} \]

331

\[ {}2 y^{\prime \prime }+9 y = 2 \cos \left (3 x \right )+3 \sin \left (3 x \right ) \]

332

\[ {}y^{\prime \prime \prime }+4 y^{\prime } = 3 x -1 \]

333

\[ {}y^{\prime \prime \prime }+y^{\prime } = 2-\sin \left (x \right ) \]

334

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = {\mathrm e}^{x} \sin \left (x \right ) \]

335

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime }+y = x \,{\mathrm e}^{x} \]

336

\[ {}y^{\left (5\right )}+5 y^{\prime \prime \prime \prime }-y = 17 \]

337

\[ {}y^{\prime \prime }+9 y = 2 x^{2} {\mathrm e}^{3 x}+5 \]

338

\[ {}y^{\prime \prime }+y = \sin \left (x \right )+x \cos \left (x \right ) \]

339

\[ {}y^{\prime \prime \prime \prime }-y^{\prime \prime }+4 y = {\mathrm e}^{x}-{\mathrm e}^{2 x} x \]

340

\[ {}y^{\left (5\right )}+2 y^{\prime \prime \prime }+2 y^{\prime \prime } = 3 x^{2}-1 \]

341

\[ {}y^{\prime \prime \prime }-y = {\mathrm e}^{x}+7 \]

342

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = {\mathrm e}^{x} \sin \left (x \right ) \]

343

\[ {}y^{\left (5\right )}-y^{\prime \prime \prime } = {\mathrm e}^{x}+2 x^{2}-5 \]

344

\[ {}y^{\prime \prime }+4 y = 3 x \cos \left (2 x \right ) \]

345

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }-12 y^{\prime } = x -2 x \,{\mathrm e}^{-3 x} \]

346

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = x \left ({\mathrm e}^{-x}-{\mathrm e}^{-2 x}\right ) \]

347

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = x \,{\mathrm e}^{3 x} \sin \left (3 x \right ) \]

348

\[ {}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+4 y = \sin \left (x \right )+\cos \left (2 x \right ) \]

349

\[ {}y^{\prime \prime \prime \prime }+9 y^{\prime \prime } = \left (x^{2}+1\right ) \sin \left (3 x \right ) \]

350

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime }+y = x^{2} \cos \left (x \right ) \]

351

\[ {}y^{\prime \prime }+4 y = 2 x \]

352

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{x} \]

353

\[ {}y^{\prime \prime }+9 y = \sin \left (2 x \right ) \]

354

\[ {}y^{\prime \prime }+y = \cos \left (x \right ) \]

355

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 1+x \]

356

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime } = x^{2} \]

357

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }+y^{\prime } = 1+x \,{\mathrm e}^{x} \]

358

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = \sin \left (3 x \right ) \]

359

\[ {}y^{\prime \prime \prime }+y^{\prime \prime } = x +{\mathrm e}^{-x} \]

360

\[ {}y^{\prime \prime \prime \prime }-y = 5 \]

361

\[ {}y^{\prime \prime \prime \prime }-y^{\prime \prime \prime }-y^{\prime \prime }-y^{\prime }-2 y = 8 x^{5} \]

362

\[ {}y^{\prime \prime \prime \prime }+4 y = \cos \left (x \right )^{3} \]

363

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \sin \left (3 x \right ) \]

364

\[ {}y^{\prime \prime }+9 y = \sin \left (x \right )^{4} \]

365

\[ {}y^{\prime \prime }+y = x \cos \left (x \right )^{3} \]

366

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 4 \,{\mathrm e}^{x} \]

367

\[ {}y^{\prime \prime }-2 y^{\prime }-8 y = 3 \,{\mathrm e}^{-2 x} \]

368

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 2 \,{\mathrm e}^{2 x} \]

369

\[ {}y^{\prime \prime }-4 y = \sinh \left (2 x \right ) \]

370

\[ {}y^{\prime \prime }+4 y = \cos \left (3 x \right ) \]

371

\[ {}y^{\prime \prime }+9 y = \sin \left (3 x \right ) \]

372

\[ {}y^{\prime \prime }+9 y = 2 \sec \left (3 x \right ) \]

373

\[ {}y^{\prime \prime }+y = \csc \left (x \right )^{2} \]

374

\[ {}y^{\prime \prime }+4 y = \sin \left (x \right )^{2} \]

375

\[ {}y^{\prime \prime }-4 y = x \,{\mathrm e}^{x} \]

376

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = 72 x^{5} \]

377

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = x^{3} \]

378

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = x^{4} \]

379

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+3 y = 8 x^{{4}/{3}} \]

380

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+y = \ln \left (x \right ) \]

381

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = x^{2}-1 \]

382

\[ {}y^{\prime \prime }+y = 2 \sin \left (x \right ) \]

383

\[ {}x^{\prime \prime }+9 x = 10 \cos \left (2 t \right ) \]

384

\[ {}x^{\prime \prime }+4 x = 5 \sin \left (3 t \right ) \]

385

\[ {}x^{\prime \prime }+100 x = 225 \cos \left (5 t \right )+300 \sin \left (5 t \right ) \]

386

\[ {}x^{\prime \prime }+25 x = 90 \cos \left (4 t \right ) \]

387

\[ {}m x^{\prime \prime }+k x = F_{0} \cos \left (\omega t \right ) \]

388

\[ {}x^{\prime \prime }+4 x^{\prime }+4 x = 10 \cos \left (3 t \right ) \]

389

\[ {}x^{\prime \prime }+3 x^{\prime }+5 x = -4 \cos \left (5 t \right ) \]

390

\[ {}2 x^{\prime \prime }+2 x^{\prime }+x = 3 \sin \left (10 t \right ) \]

391

\[ {}x^{\prime \prime }+3 x^{\prime }+3 x = 8 \cos \left (10 t \right )+6 \sin \left (10 t \right ) \]

392

\[ {}x^{\prime \prime }+4 x^{\prime }+5 x = 10 \cos \left (3 t \right ) \]

393

\[ {}x^{\prime \prime }+6 x^{\prime }+13 x = 10 \sin \left (5 t \right ) \]

394

\[ {}x^{\prime \prime }+2 x^{\prime }+26 x = 600 \cos \left (10 t \right ) \]

395

\[ {}x^{\prime \prime }+8 x^{\prime }+25 x = 200 \cos \left (t \right )+520 \sin \left (t \right ) \]

396

\[ {}x^{\prime \prime }+2 x^{\prime }+2 x = 2 \cos \left (\omega t \right ) \]

397

\[ {}x^{\prime \prime }+4 x^{\prime }+5 x = 10 \cos \left (\omega t \right ) \]

398

\[ {}x^{\prime \prime }+6 x^{\prime }+45 x = 50 \cos \left (\omega t \right ) \]

399

\[ {}x^{\prime \prime }+10 x^{\prime }+650 x = 100 \cos \left (\omega t \right ) \]

400

\[ {}y^{\prime } = y \]